Bridging histories, forging connections: African immigrants as intercultural mediators in São Paulo - Zeila de Brito Fabri Demartini; Issaka Maïnassara Bano (Educazione Interculturale, 2024)
Understanding the field of education in a broad sense, this communication addresses forms of intercultural education developed by African immigrants in their role as cultural mediators between Africa and Brazil. It is part of a research project on displacements from Africa to São Paulo, in which life stories (Ferrarotti, 1983) were collected from immigrants from regions that were colonized by European countries (Portugal and France) and who came into contact in the new context with a society that carries the marks of centuries of enslavement of black African people (Balandier, 2013; Bastide and Fernandes, 2008; Demartini, 2020a). The problems they began to experience led many to reflect on ways to address them in order to disseminate their own vision of themselves, Africa, and propose changes in society. With clear objectives, but which fall within what can be called non-formal education, they constitute themselves as cultural mediators, exercising intercultural education (Gohn, 2022). To this end, immigrants have sought in a variety of ways to preserve their practices and traditions, exercising cultural mediation in the context of São Paulo.